We don’t know what we don’t measure: A systematic review of post-harvest fish processing technology impact on social justice - Thakur, Sudarshan (University of East Anglia, 2023)
Fisheries and aquaculture are crucial sources of livelihood, food and nutrition—particularly for the global poor. Despite significant value in food systems, over one-third of the global aquatic harvest is currently lost or wasted. Appropriate postharvest practices and technology are crucial to reducing this loss and waste, improving quality and food safety, and extending shelf life and year-round availability. The lives of postharvest fisheries actors, over half of whom are women, are deeply affected by these technologies and wider changes in the sector. While the Blue Economy approach has focused on sustainability of ocean ecosystems and associated economic activities, there appears to be little attention on the postharvest sector and almost none on the equity and equality impacts on postharvest actors. As such, this systematic review focuses on the equity and equality outcomes of postharvest fish-processing technologies. We note trade-offs between enhanced productivity and incomes with the introduction of mechanized, formal technologies, and gender equality—as seen in women’s control over resources and decision-making agency— with more traditional, informal technologies. We call for more data disaggregation and rigorous research to better understand the processes and outcomes of postharvest technologies on social justice outcomes alongside livelihood, food and health security